Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst and preparation method and application thereof

Through the six-point structure of Ni-Co-Cu-Fe-In-M high-entropy intermetallic compound catalyst, the problem of low conversion rate and selectivity of existing catalysts in the hydrogenation of carbon dioxide to methanol is solved, and high efficiency is achieved methanol production and low-cost production have good industrial application prospects.

CN118950014BActive Publication Date: 2025-01-07EAST CHINA UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411441455.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing catalysts have low conversion rates, low methanol selectivity and yield in the hydrogenation of carbon dioxide to methanol, and the preparation process is complex and costly, making it difficult to meet industrial needs.

Method used

Using Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst, a hexagonal site is formed by mixing magnesium-aluminum metal oxides as support. Structure, regulates the geometric structure and electron position of active sites, and improves catalytic activity and selectivity.

Benefits of technology

A catalyst with high activity, high selectivity and high stability has been achieved. The conversion rate of carbon dioxide at low temperatures reaches close to 10%, and the selectivity of methanol reaches 100%, which reduces the production cost of the catalyst and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118950014B_ABST
    Figure CN118950014B_ABST
Patent Text Reader

Abstract

The present invention provides a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst and a preparation method and application thereof. The high entropy intermetallic compound catalyst is a magnesium-aluminum metal mixed oxide MgAlO x As a carrier, metal Ni, Co, Cu, Fe, In and M are loaded, wherein M is one of Cr, Ga and Sn, and the six metals of the high entropy intermetallic compound catalyst are orderly arranged in a parallelogram unit cell and interconnected, wherein Ni, Co, Cu and Fe are in electron-rich sites, and In and M are in electron-deficient sites, forming a six-fold site structure together. The Ni‑Co‑Cu‑Fe‑In‑M high entropy intermetallic compound catalyst of the present invention is applied to the reaction of carbon dioxide catalytic selective hydrogenation, and has the characteristics of high carbon dioxide hydrogenation catalytic activity, good methanol selectivity and long service life, and can significantly improve the methanol reaction selectivity, and avoid the generation of CO in the reverse water gas shift side reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst and a preparation method and application thereof. Background Art

[0002] Traditional methanol production mainly relies on fossil fuels, especially natural gas or coal, and a large amount of CO2 emissions are generated during the production process. As the global energy structure transforms to renewable energy, reducing the use of fossil energy and carbon emissions has become a mainstream trend. In this context, green methanol can be used as a low-carbon fuel to replace traditional fossil fuels and is widely used in chemical, transportation, energy and other fields. Especially in the fields of shipping and heavy transportation, green methanol is an ideal alternative fuel because it has a lower carbon footprint and is easy to transport and store. The production of green methanol involves a variety of technologies, such as wind or solar-driven electrolysis of water to produce green hydrogen, CO2 capture and utilization in air or industrial waste gas, and biomass conversion. Among them, the key is the efficient generation of green methanol from CO2 and green hydrogen under the action of catalysts.

[0003] Cu / ZnO / Al2O3 is a widely used commercial catalyst for methanol synthesis. Studies have shown that Cu-based catalysts are inexpensive and have good activity, but due to their poor thermal stability, the generation of water during the hydrogenation reaction will aggravate the sintering of Cu species, making it difficult to meet the needs of industrial production. In addition to Cu-based catalysts, Pd, Ni, In2O3 and Au all have certain catalytic hydrogenation activity, but the high loading and large usage of precious metal catalysts result in high catalyst use costs. In2O3 has a low conversion rate at low temperatures, and researchers have begun to pay attention to the properties of non-precious metal Ni in recent years. For example, the journal ACS Catalysis.2021 Vol. 11 No. 18, pp. 11371-11384, and the journal title "The Application of Ni-In Synergistic Effect in the Hydrogenation of Carbon Dioxide to Methanol" reported the modification of the Ni active site by the second active metal component, regulating the geometric structure and electronic properties of the Ni catalyst, thereby improving the reaction conversion rate and methanol selectivity. However, due to the low structural adjustability of binary Ni-based catalysts, the activity and selectivity of CO2 hydrogenation are not ideal, and the low methanol selectivity will increase the energy consumption of subsequent methanol separation and refining. Therefore, it is urgent to further develop new and efficient catalysts to achieve the directional conversion of CO2 catalytic hydrogenation into methanol. Summary of the invention

[0004] In view of the shortcomings of the current catalyst preparation technology, the first purpose of the present invention is to provide a new catalyst with high activity, high selectivity and high stability; the second purpose of the present invention is to provide a method for preparing the catalyst to solve the problems of complex catalyst preparation process and high production cost in the existing catalyst preparation process; the third purpose of the present invention is to provide an application of the catalyst in the reaction of hydrogenating carbon dioxide to produce methanol to solve the problems of low carbon dioxide conversion rate, low methanol selectivity and low yield in the existing reaction of hydrogenating carbon dioxide to produce methanol.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention is to provide a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst, wherein the high entropy intermetallic compound catalyst uses a magnesium-aluminum metal mixed oxide as a carrier and loads metals Ni, Co, Cu, Fe, In and M;

[0007] Among them, M is an inert metal and is selected from one of Cr, Ga, and Sn; the six metals of the high entropy intermetallic compound catalyst are orderly arranged in a parallelogram unit cell and interconnected, wherein Ni, Co, Cu and Fe are in electron-rich sites, and In and M are in electron-deficient sites, together forming a six-fold site structure; the molar ratio of the metals Ni, Co, Cu, Fe, In, and M is 1: (0.95~1.05): (0.95~1.05): (0.95~1.05): (0.95~1.05) and together form Ni-Co-Fe-Cu-In-M high entropy alloy nanoparticles of the orthorhombic hexagonal system.

[0008] The Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention forms a surface active site with a unique structure through six metals Ni, Co, Cu, Fe, In and M in the catalyst, and jointly regulates the geometric structure and electronic position of the active site, thereby forming an active site that is beneficial to the hydrogenation of carbon dioxide to methanol; wherein the localized electron cloud structure of the active metals Ni, Co, Cu and Fe is regulated by the low electronegativity inert metals In and M, so that Ni, Co, Cu and Fe are in the electron-rich site, and In and M are in the electron-deficient site, thereby jointly forming a sextuple site structure, and the synergistic effect of the sextuple site strengthens the adsorption activation of the reactant CO2 on the Ni-Fe bridge site, the H 2 adsorption and dissociation on Cu-M and Co-In bridge sites are conducive to the subsequent selective hydrogenation reaction; thanks to the regulation of Cu-M and Co-In bridge sites on the geometry and electronic properties of Ni-Fe bridge sites, the adsorption energy of product methanol and water is reduced, the adsorption of H2O on the active sites is weakened, the sintering of the active sites of the catalyst is avoided, the occurrence of insufficient stability, and the synergistic catalytic hydrogenation of CO2 to produce methanol; compared with the traditional binary nickel-based catalyst, the Ni-Co-Cu-Fe-In-M high entropy metal compound catalyst of the present invention has the characteristics of good catalytic activity, good methanol selectivity, and long life due to the introduction of multiple active and inert components, so that CO2 can reach a conversion rate of nearly 10% and a methanol selectivity of 100% at low temperature (<240 ºC), avoiding the high temperature to aggravate the generation of CO and CH4. At the same time, the use of non-precious metals as synthetic materials greatly reduces the cost of existing CO2 selective methanol catalysts, and has good industrial application prospects.

[0009] The second aspect of the present invention is to provide a method for preparing the above-mentioned Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst, comprising the following steps:

[0010] S1. When M is Cr or Ga, nitrates of Ni, Co, Cu, Fe, In, M, Mg and Al are prepared into a first solution, wherein the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the first solution is 1:(0.95-1.05):(0.95-1.05):(0.95-1.05):(0.95-1.05):(0.95-1.05):(14-17):(4-6), and Ni / Co / Cu / Fe / In / M / Mg / Al octal layered double hydroxide is prepared by coprecipitation method; when M is Sn, Ni, Co, Cu, Fe, I Nitrate of n, Mg and Al is prepared into a second solution, and tin tetrachloride pentahydrate is prepared into a third solution; the molar ratio of Ni, Co, Cu, Fe, In, Mg, Al ions in the second solution to M ions in the third solution is Ni: Co: Cu: Fe: In: M: Mg: Al = 1: (0.95-1.05): (0.95-1.05): (0.95-1.05): (0.95-1.05): (0.95-1.05): (14-17): (4-6); a Ni / Co / Cu / Fe / In / M / Mg / Al octavalent layered double hydroxide solution is prepared by a step-by-step coprecipitation method;

[0011] S2. When M is Cr or Ga, the Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution obtained in step S1 is vacuum filtered, washed, and dried to obtain a block solid Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide material; when M is Sn, the Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution obtained in step S1 is vacuum filtered, washed, and dried to obtain a filter cake that is in situ grown in a 0.1-0.5 mol / L Na2CO3 solution, and the previous vacuum filtration, washing, and drying are repeated to obtain a block solid Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide material;

[0012] S3. The block solid Ni / Co / Cu / Fe / In / M / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment to obtain a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst.

[0013] The method for preparing a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention utilizes the main layer plate composition and element adjustable characteristics of a layered double hydroxide material to prepare a Ni / Co / Cu / Fe / In / M / Mg / Al octal layered double hydroxide material, and combines a subsequent thermal reduction process to achieve controllable preparation of different Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalysts; during the thermal reduction treatment process, high entropy alloy metal particles Ni-Co-Cu-Fe-In-M and Mg-Al-O (MgO and MgAl2O4) metal oxides are simultaneously generated, so that a strong interaction exists between the generated alloy particles and the metal oxides, thereby avoiding the metal particle agglomeration phenomenon caused by high-temperature roasting and high-temperature thermal reduction in the traditional impregnation method, thereby improving the utilization rate of active components Ni, Co, Cu, Fe, and In, and improving the catalytic activity. The method for preparing a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention has active sites that are beneficial to methanol generation and inhibit CO generation, and has extremely high methanol selectivity, effectively solving the limitation of low selectivity of non-precious metal catalyst hydrogenation performance. At the same time, the method adopts non-precious metals as synthetic materials, greatly reducing the production cost of existing carbon dioxide hydrogenation to methanol catalysts, and has good industrial application prospects.

[0014] Further, in step S1, when M is Cr or Ga, the co-precipitation method is to prepare Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide by simultaneously adding the first solution and the pH regulator to the precipitant under stirring, and the addition rate of the first solution is 0.9±0.2mL / min; the temperature of the reaction system is maintained at 60~70°C, and the pH value of the reaction system is controlled to be 10±0.1; after the addition is completed, the stirring reaction is continued for 14~18h to obtain a Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution;

[0015] When M is Sn, the step-by-step co-precipitation method for preparing Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered double hydroxide is to simultaneously add a second solution and a pH regulator to the precipitant under stirring conditions, and the addition rate of the second solution is 0.9±0.2 mL / min; the temperature of the reaction system is maintained at 60~70°C and the pH value of the reaction system is controlled to 10±0.1 to obtain a fourth solution; the third solution and the pH regulator are simultaneously added to the fourth solution, and the addition rate of the third solution is 0.9±0.2 mL / min; the temperature of the reaction system is maintained at 60~70°C and the pH value of the reaction system is controlled to 10±0.1 until the addition is completed, and the reaction is continued to stir for 14~18 hours to obtain a Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered double hydroxide solution.

[0016] Furthermore, in step S1, when M is Cr or Ga, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg, and Al ions in the first solution is 1:1:1:1:1:1:(14-17):(4-6); when M is Sn, the molar ratio of Ni, Co, Cu, Fe, In, Mg, and Al ions in the second solution to M ions in the third solution is Ni:Co:Cu:Fe:In:M:Mg:Al=1:1:1:1:1:1:(14-17):(4-6);

[0017] The concentration of nickel ions in the first solution and the second solution is 0.02-0.05 mol / L;

[0018] The nitrates of Ni, Fe, Co, Cu, In, Cr, Ga, Mg and Al are nickel nitrate hexahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, copper nitrate trihydrate, indium nitrate nonahydrate, chromium nitrate nonahydrate, gallium nitrate nonahydrate, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate respectively;

[0019] The precipitant is one of sodium carbonate solution, ammonia water, sodium bicarbonate solution, potassium carbonate solution and potassium bicarbonate solution; the pH adjuster is one of sodium bicarbonate solution, potassium hydroxide solution and sodium hydroxide solution.

[0020] Furthermore, in step S2, the vacuum filtration conditions are: using ordinary filter paper as the filter membrane, the vacuum degree is 0.05~0.08MPa; the drying conditions are: temperature 80±5°C, drying 6~18h.

[0021] Furthermore, in step S1, the addition rate of the first solution, the second solution, and the third solution is 1.0 mL / min; the pH adjuster is a sodium hydroxide solution with a molar concentration of 2.5±0.2 mol / L, and during the addition process, the pH value of the reaction system is controlled to be 10±0.1.

[0022] Furthermore, in step S3, the temperature of the thermal reduction treatment is 600-1000 °C, the reduction time is 2-6 hours, and the reducing gas is a H2 / Ar mixed atmosphere.

[0023] When the thermal reduction temperature is lower than 600°C, the reduction reaction rate is slow, the high entropy alloy Ni-Co-Cu-Fe-In-M metal particles grow slowly, and the particle size is smallest. The smaller Ni-Co-Cu-Fe-In-M particles can easily penetrate into the pores of the Mg-Al oxide carrier, resulting in a decrease in the dispersion measured by chemical adsorption and a decrease in the number of active sites on the catalyst surface, resulting in poor catalyst effect; when the thermal reduction temperature is higher than 1000°C, the reduction reaction rate is fast, the Ni-Co-Cu-Fe-In-M particles grow faster, the particle size is larger, the dispersion measured by chemical adsorption is reduced, the number of active sites on the catalyst surface is reduced, and the catalytic effect is poor.

[0024] Furthermore, in step S3, the temperature of the thermal reduction treatment is 800 °C and the reduction time is 4 h.

[0025] When the reduction temperature is 800°C, the reduction reaction rate is moderate, and the obtained Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst Ni-Co-Cu-Fe-In-M particles are uniformly loaded on the carrier surface, the dispersion measured by chemical adsorption is the highest, the number of active sites on the catalyst surface is the largest, and the catalytic effect is better.

[0026] The third aspect of the present invention is to provide an application of the above-mentioned Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst in the catalytic hydrogenation of carbon dioxide to methanol reaction, and the reaction conditions of the catalytic hydrogenation of carbon dioxide to methanol reaction include: a reaction temperature of 200~240°C and a pressure of 3~10MPa; the composition of the raw gas is: 20~24% carbon dioxide, 60~72% hydrogen, and the balance gas is argon.

[0027] The Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention is used for catalytic hydrogenation of carbon dioxide to prepare methanol. Compared with the use of existing binary Ni-based catalysts, the methanol selectivity and yield are significantly improved. At 200-240° C., the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention has extremely high methanol selectivity.

[0028] Furthermore, the reaction temperature of the carbon dioxide catalytic hydrogenation reaction to produce methanol is 230-240° C. and the pressure is 3 MPa.

[0029] When the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention is used to catalyze the hydrogenation of carbon dioxide to prepare methanol, a relatively high carbon dioxide conversion rate and a methanol yield can be simultaneously obtained when the reaction temperature is 230-240°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the XRD spectrum of catalyst X2-800-4 prepared in Example 2.

[0031] Figure 2 It is a high-resolution transmission electron microscope image of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 and the corresponding atomic image intensity distribution map.

[0032] Figure 3 This is a high-angle annular dark field scanning transmission electron microscope image of a certain position of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 and the corresponding EDS surface scanning elemental analysis image.

[0033] Figure 4 This is a high-angle annular dark field scanning transmission electron microscope image of another position of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 and the corresponding EDS surface scanning elemental analysis image.

[0034] Figure 5 It is a high-angle annular dark field scanning transmission electron microscope image of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 and an EDS line scan elemental analysis image of the corresponding particles.

[0035] Figure 6 The spherical aberration electron microscope image and the corresponding atomic image intensity distribution map of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 are as follows (along Figure 6 The Fourier transform diagram is shown in the direction of the arrow.

[0036] Figure 7 for Figure 6 A magnified view of the marked area and a crystal model corresponding to the

[002] zone axis projection.

[0037] Figure 8 This is a two-dimensional differential charge analysis diagram of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2.

[0038] Fig. 9 This is a high-angle annular dark field scanning transmission electron microscopy image of a certain position of the Ni2In intermetallic compound catalyst X12-800-4 prepared in Comparative Example 1 and the corresponding EDS surface scanning elemental analysis image.

[0039] Fig.10 This is a high-angle annular dark field scanning transmission electron microscopy image of another position of the Ni2In intermetallic compound catalyst X12-800-4 prepared in Comparative Example 1 and the corresponding EDS surface scanning elemental analysis image.

[0040] Fig.11 This is a high-resolution transmission electron micrograph of the Ni2In intermetallic compound catalyst X12-800-4 prepared in Comparative Example 1.

[0041] Fig.12 for Fig.11 Atomic image intensity distribution diagram of the enlarged area in the figure.

[0042] Fig.13 This is the EDS line scan element analysis diagram of the Ni2In intermetallic compound catalyst X12-800-4 prepared in Comparative Example 1 along the direction of the arrow. DETAILED DESCRIPTION

[0043] The present invention will be further described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example 1

[0044] The preparation of the Ni-Co-Cu-Fe-In-Cr high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0045] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.00 g of chromium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Cr: Mg: Al = 1:1:1:1:1:1:16:4;

[0046] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0047] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0048] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65 ° C for 1 h, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and the addition rate of the first solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and the addition rate of the pH regulator was controlled by a constant flow pump to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0 ± 0.1; during the addition process, the temperature of the reaction system was controlled to be constant at 65 ° C. After the addition was completed, the reaction system was continuously and vigorously stirred at a temperature of 65 ° C for 16 h to obtain a Ni / Co / Cu / Fe / In / Cr / Mg / Al octa-element layered double hydroxide solution;

[0049] S2. The Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Cr / Mg / Al octa-layered double hydroxide material;

[0050] S3. The Ni / Co / Cu / Fe / In / Cr / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Cr high entropy intermetallic compound catalyst, which is recorded as X1-800-4. Example 2

[0051] The preparation of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0052] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:16:4;

[0053] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0054] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0055] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0056] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0057] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X2-800-4. Example 3

[0058] The preparation of the Ni-Co-Cu-Fe-In-Sn high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0059] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a second solution, in which the molar ratio of the metal ions in the second solution was Ni: Co: Cu: Fe: In: Mg: Al = 1:1:1:1:1:16:4;

[0060] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0061] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0062] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65° C. for 1 h, and then the second solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the second solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the addition process, the temperature of the reaction system was controlled to be constant at 65° C. to obtain a fourth solution;

[0063] Tin tetrachloride pentahydrate was configured into a 0.11 mol / L tin chloride aqueous solution as the third solution; the temperature of the fourth solution was maintained at 65°C, 30 ml of the third solution was added to the fourth solution, and a constant flow pump was used to control the addition rate of the third solution to be 0.8 mL / min, and a pH regulator was added to the fourth solution so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C until the feeding was completed; after the feeding was completed, the stirring was continued vigorously at a temperature of 65°C for 16 h to obtain a Ni / Co / Cu / Fe / In / Sn / Mg / Al octa-element layered double hydroxide solution;

[0064] S2. The Ni / Co / Cu / Fe / In / Sn / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered by a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after filtration is dried at 110°C for 12h, and the dried filter cake is in situ grown in 200 mL of a 0.1 mol / L Na2CO3 solution (the in situ growth temperature is 35°C, and the time is 12h), and then the previous vacuum filtration, washing, and drying are repeated to obtain a green block solid Ni / Co / Cu / Fe / In / Sn / Mg / Al octa-layered double hydroxide material;

[0065] S3. The Ni / Co / Cu / Fe / In / Sn / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Sn high entropy intermetallic compound catalyst, which is recorded as X3-800-4. Example 4

[0066] The preparation of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0067] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:16:4;

[0068] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0069] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0070] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0071] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0072] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 600°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, recorded as X4-600-4. Example 5

[0073] The preparation of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0074] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:16:4;

[0075] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0076] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0077] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0078] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0079] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 1000°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X5-1000-4. Example 6

[0080] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:16:4;

[0081] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0082] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0083] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0084] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0085] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 2h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X6-800-2. Example 7

[0086] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 10.26 g of magnesium nitrate hexahydrate, and 3.7513 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:16:4;

[0087] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0088] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0089] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0090] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0091] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X7-800-6. Example 8

[0092] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 9.615 g of magnesium nitrate hexahydrate, and 4.689 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:15:5;

[0093] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0094] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0095] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0096] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0097] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, recorded as X8-800-4. Example 9

[0098] S1. 0.7270 g of nickel nitrate hexahydrate, 0.7276 g of cobalt nitrate hexahydrate, 0.604 g of copper nitrate trihydrate, 1.01 g of iron nitrate nonahydrate, 1.1576 g of indium nitrate nonahydrate, 1.045 g of gallium nitrate nonahydrate, 8.974 g of magnesium nitrate hexahydrate, and 5.6269 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, in which the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1:1:1:1:1:1:14:6;

[0099] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0100] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0101] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0102] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0103] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X9-800-4. Example 10

[0104] The preparation of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0105] S1. 0.7270 g of nickel nitrate hexahydrate, 0.6912 g of cobalt nitrate hexahydrate, 0.5738 g of copper nitrate trihydrate, 0.9595 g of iron nitrate nonahydrate, 1.10 g of indium nitrate nonahydrate, 0.9928 g of gallium nitrate nonahydrate, 9.747 g of magnesium nitrate hexahydrate, and 3.5637 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, wherein the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1: 0.95: 0.95: 0.95: 0.95: 0.95: 16:4;

[0106] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0107] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0108] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0109] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0110] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X10-800-4. Embodiment 11

[0111] The preparation of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst of this embodiment includes the following steps:

[0112] S1. 0.7270 g of nickel nitrate hexahydrate, 0.764 g of cobalt nitrate hexahydrate, 0.6342 g of copper nitrate trihydrate, 1.06 g of iron nitrate nonahydrate, 1.2155 g of indium nitrate nonahydrate, 1.097 g of gallium nitrate nonahydrate, 10.773 g of magnesium nitrate hexahydrate, and 3.9388 g of aluminum nitrate nonahydrate were dissolved in 100 ml of ultrapure water and dispersed by ultrasonic to obtain a first solution, wherein the molar ratio of the metal ions in the first solution is Ni: Co: Cu: Fe: In: Ga: Mg: Al = 1: 1.05: 1.05: 1.05: 1.05: 1.05: 16:4;

[0113] Dissolve 4.24 g of sodium carbonate powder in 100 ml of ultrapure water and disperse by ultrasonic to obtain a precipitant;

[0114] Dissolve 20.00 g of sodium hydroxide powder in 200 ml of ultrapure water and disperse by ultrasonic to obtain a pH adjuster;

[0115] The precipitant was transferred to a 500 ml three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour, and then the first solution was added dropwise to the precipitant at a speed of 140 r / min, and a constant flow pump was used to control the addition rate of the first solution to be 1.0 mL / min; at the same time, a pH regulator was added to the precipitant, and a constant flow pump was used to control the addition rate of the pH regulator to be 0.8 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1; during the feeding process, the temperature of the reaction system was controlled to be constant at 65°C. After the feeding was completed, continuous and vigorous stirring was continued at a temperature of 65°C for 16 hours to obtain a Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution;

[0116] S2. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide solution obtained in step S1 is filtered using a vacuum filter (using ordinary filter paper as the filter membrane, and the vacuum degree is 0.05 MPa), and washed with pure water while filtering. The filtration is stopped after washing until the filtrate is clear and the pH is neutral. The filter cake obtained after the filtration is dried at 110° C. for 12 hours to obtain a grass-green block solid Ni / Co / Cu / Fe / In / Ga / Mg / Al octa-layered double hydroxide material;

[0117] S3. The Ni / Co / Cu / Fe / In / Ga / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment (the thermal reduction temperature is 800°C, the reduction time is 4h, and the reducing gas is a H2 / Ar mixed atmosphere (volume ratio 1:4)) to obtain a Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, which is recorded as X11-800-4.

[0118] Comparative Example 1

[0119] The preparation of the Ni2In intermetallic compound catalyst of this comparative example comprises the following steps:

[0120] (1) 1.94 g Ni(NO3)2·6H2O, 1.36 g In(NO3)3·9H2O, 12.82 g Mg(NO3)2·6H2O and 6.25 g Al(NO3)3·9H2O were dissolved in 100 mL ultrapure water and dispersed by ultrasonic, which was recorded as a mixed metal nitrate solution. The molar ratio of Ni, In, Mg and Al ions was 2:1:15:5.

[0121] 4.24 g of Na2CO3 powder was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic to obtain a precipitant;

[0122] 20.00 g of NaOH powder was dissolved in 200 mL of ultrapure water and dispersed by ultrasonic to obtain a pH regulator;

[0123] The precipitant was transferred to a 500 mL three-necked flask and placed in an oil bath at 65 ° C for constant temperature treatment for 1 h, and then the mixed metal nitrate solution of step (1) was added dropwise at a speed of 160 r / min, and the flow rate was controlled to 1.0 mL / min by a constant flow pump; at the same time, a pH regulator was added by a constant flow pump, and the flow rate was controlled to 1.2 mL / min, so that the pH of the reaction system in the three-necked flask was constant at 10.0±0.1. After the feeding was completed, the mixture was continuously and vigorously stirred at a synthesis temperature of 65 ° C for 16 h, and then vacuum filtered and washed several times until the pH was neutral to obtain a green block solid Ni / In / Mg / Al quaternary layered double hydroxide material;

[0124] (2) The Ni / In / Mg / Al quaternary layered double hydroxide material prepared in step (1) was reduced at 800°C in a H2 / N2 atmosphere (volume ratio 1:4) for 4 h to obtain a Ni2In intermetallic compound catalyst, which was recorded as X12-800-4.

[0125] Catalyst characterization: The XRD spectrum of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst X2-800-4 prepared in Example 2 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the high entropy intermetallic compounds prepared in the present invention have obvious crystal structures, and the diffraction intensity of the (110) crystal plane is the highest, and its distribution on the surface of the high entropy alloy particles accounts for the largest proportion; the high-resolution transmission electron microscope image of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst X2-800-4 prepared in Example 2 and the corresponding atomic image intensity distribution diagram are shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the high entropy intermetallic compound catalyst prepared by the present invention has obvious lattice fringes and Figure 2 The lattice spacing of the enlarged area in the left image is 0.21nm, which also verifies Figure 1 The XRD results show that the synthesized catalyst has an obvious crystal structure. The Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 was subjected to elemental analysis, and high-angle annular dark field scanning transmission electron microscopy images at two different positions and the corresponding EDS surface scanning elemental analysis images were obtained as shown in the figure. Figure 3 , Figure 4 As shown, from Figure 3 , Figure 4 It can be seen that in the Ni-Co-Cu-Fe-In-Ga catalyst prepared by the present invention, the elements Ni, Co, Cu, Fe, In, and Ga are evenly distributed, indicating that a Ni-Co-Cu-Fe-In-Ga six-element alloy crystal phase is formed in the catalyst; Figure 5 The high-angle annular dark field scanning transmission electron microscope image of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 and the EDS line scan element analysis image of the corresponding particles are shown in FIG. Figure 5 It can be seen that in the Ni-Co-Cu-Fe-In-Ga catalyst prepared in Example 2, the atomic ratio of each metal element (Ni, Co, Cu, Fe, In, Ga) is close to 1:1:1:1:1:1; Figure 6 The spherical aberration electron microscope image and the corresponding atomic image intensity distribution map of the Ni-Co-Cu-Fe-In-Ga catalyst X2-800-4 prepared in Example 2 are as follows (along Figure 6 The Fourier transform diagram is shown in the direction of the arrow in the middle. Figure 6 It can be seen that the lattice spacing along the arrow direction in the left figure is 0.21nm, corresponding to the (110) plane of the Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst, the crystal region

[002] . It should be noted that the atomic radii of the elements Ni, Co, Cu, Fe, and In are close, and the lattice spacing has not changed significantly; Figure 7 for Figure 6 The enlarged view of the rectangular marked area in the middle left figure and the crystal model corresponding to the

[002] crystal zone axis projection, from Figure 7 It can be seen that the atomic arrangement of the catalyst particles is highly consistent with the results of the Ni-Co-Cu-Fe-In-Ga density functional theory simulation, indicating that the six metal element sites are arranged in an orderly manner to form a six-fold site structure of Ni-Co-Cu-Fe-In-Ga.

[0126] The charge analysis of Ni-Co-Cu-Fe-In-Ga high entropy intermetallic compound catalyst X2-800-4 was performed, and the results are as follows Figure 8 As shown, the charge is enriched at the centers of the Fe, Co, Ni, and Cu quadruple sites, indicating that electrons are transferred from the inert metals In and Ga to the active metals Fe, Co, Ni, and Cu, forming a Ni-Co-Cu-Fe-In-Ga sextuple site structure with electron-rich Fe, Co, Ni, and Cu and isolated electron-deficient In and Ga.

[0127] The elemental analysis of the Ni2In intermetallic compound catalyst prepared in Comparative Example 1 was performed, and the results were as follows: Fig. 9 , Fig.10 As shown, the elements In, Ni, Mg, and Al are evenly distributed;

[0128] Fig.11 This is a high-resolution transmission electron microscopy image of the Ni2In intermetallic compound catalyst X12-800-4 prepared in Comparative Example 1. Fig.12 for Fig.11 The intensity distribution of atomic images in the enlarged area is shown in Figure 2. Fig.11 , 12 It can be seen that the Ni2In intermetallic compound catalyst prepared in Comparative Example 1 has obvious lattice fringes and Fig.11 The lattice spacing in the middle magnified area is 0.209nm; Fig.13 This is the EDS line scan element analysis diagram of the Ni2In catalyst X12-800-4 prepared in Comparative Example 1 along the direction of the arrow. It can be seen that the ratio of the metal elements Ni and In is close to 2:1.

[0129] Catalytic performance evaluation of catalyst

[0130] The Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared in Examples 1 to 11 and the Ni2In intermetallic compound catalyst prepared in Comparative Example 1 were used to evaluate the activity of the selective hydrogenation of carbon dioxide; the carbon dioxide hydrogenation reaction performance evaluation was carried out on the ZKJC-RJ-X system of Beijing Wanlonghe Technology Co., Ltd., wherein:

[0131] The components in the reactants and products were analyzed online using a 3-channel GC9790Plus (Fuli Company, China).

[0132] The chromatograph is equipped with three detectors, one is a thermal conductivity detector (TCD) with GDX-01 and GDX-02 columns for detecting non-condensable gases including H2, CO, CH4, CO2, and the other is a flame ionization detector (FID) with RB-INNOWAX columns for analyzing hydrocarbons. The comprehensive external standard method can accurately obtain the concentration of various components in the product.

[0133] Evaluation conditions: total inlet flow rate of 60 mL / min, feed gas of 24% CO2, 72% H2, 4% Ar, reaction temperature of 200-300 °C, pressure of 3 MPa; catalyst loading of 150 mg.

[0134] Weigh 150 mg of catalyst sample, mix it evenly with 350 mg of quartz sand, and then load it into the constant temperature zone of the stainless steel reaction tube. After the catalyst is loaded, first check the reaction system for leaks, and introduce a certain pressure of argon (such as 10 bar) into the reaction system. If the pressure can remain constant, it means that the reaction system has good sealing performance and can be evaluated.

[0135] Set the argon flow rate to 20 sccm (Standard Cubic Centimeter Per Minute), raise the temperature to the reduction temperature; then turn off the argon, set the hydrogen flow rate to 20 sccm, after a certain period of reduction, turn off the hydrogen; set the argon flow rate to 20 sccm, cool down to the reaction temperature, and set the pressure required for the reaction. After the reaction conditions are stable, set the flow rate of each reaction component, set the flow rate of the reaction mixed gas (CO2: H2: Ar = 24: 72: 4) to 60ml / min, and cut the furnace six-way valve to bypass, so that the mixed gas directly enters the chromatogram to detect the concentration of each component before the reaction. After stabilization, cut the furnace six-way valve back into the reaction tube to start the reaction, and the gas at the outlet of the reaction tube enters the online chromatographic detection.

[0136] The catalytic performance of the catalysts for the hydrogenation of carbon dioxide to produce methanol was evaluated by testing the carbon dioxide conversion rate, methanol selectivity, and methanol yield of the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalysts prepared in Examples 1 to 5 and the binary Ni-based catalyst (Ni2In intermetallic compound catalyst) prepared in Comparative Example 1, wherein:

[0137] Carbon dioxide hydrogenation conversion rate:

[0138]

[0139] Selectivity of CO2 hydrogenation to methanol:

[0140]

[0141] Carbon dioxide hydrogenation methanol yield:

[0142]

[0143] The test results are shown in Tables 1 to 3.

[0144] Table 1. Catalyst CO2 hydrogenation conversion rate (%)

[0145]

[0146] Table 2. Catalyst CO2 hydrogenation methanol selectivity (%)

[0147]

[0148] Table 3. Catalyst CO2 hydrogenation methanol yield (%)

[0149]

[0150] Combined with the results shown in Tables 1 to 3, it can be seen that the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst of the present invention is significantly improved in methanol selectivity and yield compared with the binary Ni-based catalyst (Ni2In intermetallic compound catalyst). In the range of 200-240°C, the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared in the embodiment has extremely high methanol selectivity, and when the temperature reaches 240°C, a high carbon dioxide conversion rate and methanol selectivity can be obtained simultaneously. It is shown that the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared by the technical solution of the present invention can significantly improve the carbon dioxide conversion rate, methanol selectivity and yield compared with the binary Ni-based catalyst.

[0151] Evaluation of Catalyst Stability for Carbon Dioxide Hydrogenation

[0152] The X2-800-4 catalyst prepared in Example 2 was randomly selected, and the stability of the catalyst was evaluated at 240°C according to the catalyst performance test method of the above-mentioned catalyst carbon dioxide hydrogenation performance evaluation experiment. The data results of C(CO2), S(CH3OH), and Y(CH3OH) are shown in Table 4.

[0153] Table 4. Evaluation of stability of X2-800-4 catalyst for carbon dioxide hydrogenation

[0154]

[0155] From the results shown in Table 4, it can be seen that after 48 hours of reaction, the carbon dioxide conversion rate of the X2-800-4 catalyst prepared in Example 2 remained at the same level, and the methanol selectivity remained at 99%, which shows that it has good stability.

[0156] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst, characterized in that: The high entropy intermetallic compound catalyst uses magnesium-aluminum metal mixed oxide as a carrier and loads metals Ni, Co, Cu, Fe, In and M; Among them, M is an inert metal and is selected from one of Cr, Ga, and Sn; the six metals of the high entropy intermetallic compound catalyst are orderly arranged in a parallelogram unit cell and interconnected, wherein Ni, Co, Cu and Fe are in electron-rich sites, and In and M are in electron-deficient sites, together forming a six-fold site structure; the molar ratio of the metals Ni, Co, Cu, Fe, In, and M is 1: (0.95~1.05): (0.95~1.05): (0.95~1.05): (0.95~1.05) and together form Ni-Co-Fe-Cu-In-M high entropy alloy nanoparticles of the orthorhombic hexagonal system.

2. A method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 1, characterized in that: The following steps are involved: S1. When M is Cr or Ga, nitrates of Ni, Co, Cu, Fe, In, M, Mg and Al are prepared into a first solution, wherein the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the first solution is 1:(0.95-1.05):(0.95-1.05):(0.95-1.05):(0.95-1.05):(0.95-1.05):(14-17):(4-6), and Ni / Co / Cu / Fe / In / M / Mg / Al octal layered double hydroxide is prepared by coprecipitation method; when M is Sn, Ni, Co, Cu, Fe, I Nitrate of n, Mg and Al is prepared into a second solution, and tin tetrachloride pentahydrate is prepared into a third solution; the molar ratio of Ni, Co, Cu, Fe, In, Mg, Al ions in the second solution to M ions in the third solution is Ni: Co: Cu: Fe: In: M: Mg: Al = 1: (0.95-1.05): (0.95-1.05): (0.95-1.05): (0.95-1.05): (0.95-1.05): (14-17): (4-6); a Ni / Co / Cu / Fe / In / M / Mg / Al octavalent layered double hydroxide solution is prepared by a step-by-step coprecipitation method; S2. When M is Cr or Ga, the Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution obtained in step S1 is vacuum filtered, washed, and dried to obtain a block solid Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide material; when M is Sn, the Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution obtained in step S1 is vacuum filtered, washed, and dried to obtain a filter cake that is in situ grown in a 0.1-0.5 mol / L Na2CO3 solution, and the previous vacuum filtration, washing, and drying are repeated to obtain a block solid Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide material; S3. The block solid Ni / Co / Cu / Fe / In / M / Mg / Al octal layered double hydroxide material obtained in step S2 is subjected to thermal reduction treatment to obtain a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst.

3. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 2, characterized in that: In the step S1, when M is Cr or Ga, the co-precipitation method is to prepare the Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide by adding the first solution and the pH regulator to the precipitant under stirring, and the addition rate of the first solution is 0.9±0.2 mL / min; the temperature of the reaction system is maintained at 60-70°C, and the pH value of the reaction system is controlled to be 10±0.1; after the addition is completed, the stirring reaction is continued for 14-18 hours to obtain a Ni / Co / Cu / Fe / In / M / Mg / Al octa-membered layered double hydroxide solution; When M is Sn, the step-by-step co-precipitation method for preparing Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered double hydroxide is to simultaneously add a second solution and a pH regulator to the precipitant under stirring conditions, and the addition rate of the second solution is 0.9±0.2 mL / min; the temperature of the reaction system is maintained at 60~70°C and the pH value of the reaction system is controlled to 10±0.1 to obtain a fourth solution; the third solution and the pH regulator are simultaneously added to the fourth solution, and the addition rate of the third solution is 0.9±0.2 mL / min; the temperature of the reaction system is maintained at 60~70°C and the pH value of the reaction system is controlled to 10±0.1 until the addition is completed, and the reaction is continued to stir for 14~18 hours to obtain a Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered double hydroxide solution.

4. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 3, characterized in that: In the step S1, when M is Cr or Ga, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg, and Al ions in the first solution is 1:1:1:1:1:1:(14-17):(4-6); when M is Sn, the molar ratio of Ni, Co, Cu, Fe, In, Mg, and Al ions in the second solution to M ions in the third solution is Ni:Co:Cu:Fe:In:M:Mg:Al=1:1:1:1:1:1:(14-17):(4-6); The concentration of nickel ions in the first solution and the second solution is 0.02-0.05 mol / L; The nitrates of Ni, Fe, Co, Cu, In, Cr, Ga, Mg and Al are nickel nitrate hexahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, copper nitrate trihydrate, indium nitrate nonahydrate, chromium nitrate nonahydrate, gallium nitrate nonahydrate, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate respectively; The precipitant is one of sodium carbonate solution, ammonia water, sodium bicarbonate solution, potassium carbonate solution and potassium bicarbonate solution; the pH adjuster is one of sodium bicarbonate solution, potassium hydroxide solution and sodium hydroxide solution.

5. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 2, characterized in that: In step S2, the vacuum filtration conditions are: using ordinary filter paper as the filter membrane, the vacuum degree is 0.05~0.08MPa; the drying conditions are: temperature 80±5°C, drying 6~18h.

6. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 4, characterized in that: In the step S1, the addition rate of the first solution, the second solution, and the third solution is 1.0 mL / min; the pH adjuster is a sodium hydroxide solution with a molar concentration of 2.5±0.2 mol / L, and during the addition process, the pH value of the reaction system is controlled to be 10±0.

1.

7. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 2, characterized in that: In step S3, the temperature of the thermal reduction treatment is 600-1000 °C, the reduction time is 2-6 hours, and the reducing gas is a H2 / Ar mixed atmosphere.

8. The method for preparing the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 2, characterized in that: In step S3, the temperature of the thermal reduction treatment is 800°C and the reduction time is 4h.

9. Use of the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst according to claim 1 or the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared by the preparation method according to any one of claims 2 to 8 in the catalytic hydrogenation of carbon dioxide to methanol reaction, characterized in that: The reaction conditions of the carbon dioxide catalytic hydrogenation to methanol reaction include: reaction temperature of 200-240° C., pressure of 3-10 MPa; composition of the raw gas: 20-24% carbon dioxide, 60-72% hydrogen, and balance gas of argon.

10. The use according to claim 9, characterized in that: The reaction conditions of the carbon dioxide catalytic hydrogenation to methanol reaction are: temperature 230-240° C., pressure 3 MPa.

Citation Information

Patent Citations

  • Supported Ni-Sb catalyst and preparation method and application thereof

    CN114849713A

  • Co-Sb-M ternary intermetallic compound catalyst and preparation method and application thereof

    CN117680153A